Strengtening R/C and masonry structures with fiber reinfirced polymers in disaster areas - Doran, Bilge; Koksal, Hasan Orhun; Akbas, Bulent (IOS PRESS, 2015)
This paper presents the use of fiber reinforced polymers (FRP) for strengthening reinforced concrete (R/C) and masonry structures in disaster areas. FRPs have gained rapid popularity in recent years as one of the strengthening techniques of structural concrete and masonry members. Although substantial experimental and analytical researches have been conducted to model and simulate the response of these members confined with FRP jackets under concentric and eccentric loading, there is still an apparent need for efficient numerical models to further understand the stress-strain behavior and failure mechanisms of the confined material. The primary aim of this paper is to introduce an effective modeling procedure for the reinforced concrete (R/C) and masonry structural members such as columns and walls under shear and/or compression.
Keywords: Fiber reinforced polymers; numerical modeling; reinforced concrete columns; masonry walls; Engineering; International Relations; Social Sciences - Other Topics